Ganti Rugi Sebagai Pertanggungjawaban Konsumen Terhadap Perbuatan Melawan Hukum Yang Merugikan Perusahaan Listrik Negara - Sri Wahyuni; Endang Hadrian; Asti Wasiska (KRTHA BHAYANGKARA, 2023)
Electricity is a very important requirement in carrying out various activities in everyday life, almost all human activities require electrical energy. In Indonesia, the business of providing electricity for the public interest is carried out by the State Electricity Company (PLN). The relationship between business actors providing electricity and consumers should refer to the principle of good faith in its implementation. However, there are several examples of cases of violations committed by electricity consumers regarding unlawful acts. This unlawful act will be very detrimental to one of the parties, namely the electricity provider in this case. For this reason, this research focuses on compensation as the consumer's responsibility for unlawful acts that cause harm to the electricity provider. In this study, the normative legal research method will be used with a case approach. The theory used to answer this research is the theory of consumer responsibility for unlawful acts that cause losses due to their mistakes. The results of this study are to determine compensation arrangements as the responsibility of electricity consumers for unlawful acts that cause losses to the electricity provider.